Effectiveness of Intensive Young Diabetes Program (IYDP) at Klinik Kesihatan Jalan Masjid (KKJM) Kuching, 2024 - Sarudu, Shareezan Hoklai; Abdullah Zawawi, Zaitul Akmal; Mustapha, Maila (International Journal of Human and Health Sciences (IJHHS), 2025)
Objective: According to the latest National Health Morbidity Survey (NHMS) 2023, 15.6% or 1 in 6 adults have diabetes in Malaysia. The prevalence of Type 2 Diabetes Mellitus (T2DM) is increasing and this includes the younger age group. Onset of a younger age is associated with longer disease exposure and increased risk for chronic complications. It also affects more individuals of working age, accentuating the adverse societal effects of the disease. Thus, the IYDP, which involves multidisciplinary team is implemented to improve the disease control and outcomes. Methods: Retrospective review of 125 cases of biopsy-proven lung cancer referred for FDG PET-CT in our institution over the past 2 years. Staging PET-CT scans (n=54) were included for analysis. Clinical parameters and PET-CT findings (SUVmax of primary lesion, presence of nodal and metastatic disease) were investigated. SUVmax of primary lesion for SCC and adenocarcinoma was compared. Association between SUVmax of primary lesion and extrapulmonary FDG- avid lesions presence was also determined. Results: Males were predominant (60%). Average age was 62.5 years. Majority were adenocarcinoma (65%) followed by SCC (22%) and others (13%). Mean tumour size was 5.1 cm. Lung SCC demonstrated intensely increased FDG uptake that was significantly higher compared to adenocarcinoma (average SUVmax 24.4 vs SUVmax 15.6, p<0.05). FDG-avid ipsilateral hilar nodal involvement was seen in 63%, mediastinal nodes in 70% while distant metastatic disease in 33%. Patients having primary lesions with SUVmax 20.0 and above were significantly associated with larger tumour size and FDG-avid ipsilateral hilar nodal uptake (p<0.05). Conclusion: Lung SCC was intensely FDG-avid and had higher SUVmax compared to adenocarcinoma. Primary lesions with SUVmax 20.0 and above were associated with larger tumour size and presence of hypermetabolic ipsilateral hilar nodal spread. Information obtained from this review will provide valuable insight into PET-CT scan characteristics of newly diagnosed NSCLC cases in our institution that may influence not only scan reporting formulation but also patient management. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S42